PENGARUH ONLINE CONSUMER REVIER, DIGITAL PAYMENT, SOCIAL MEDIA ADVERTISEMENT, DAN INFLUENCER ENDORSMENT TERHADAP PURCHASE INTENTION PADA PRODUK SKINCARE Y.O.U BEAUTY - Elvira Leonita; Deni Wardani (Ibs Press, 2024)
This study aims to test and analyze the influence of Online Consumer Review, Digital Payment, Social Media Advertisement, and Influencer Endorsement on Purchase Intention in Y.O.U Beauty skincare products. Primary data collection was carried out for 1 weeks using a research sample of 89 respondents. This study used a descriptive research design approach with empirical data collected through online surveys. Empirical data is then processed using the Structural Equation Modeling approach to test a number of hypotheses proposed. The results of this study Social Media Advertisement and Influencer Endorsement have a positive effect on Purchase Intention. Online Consumer Reviews negatively affect Purchase Intention. However, Digital Payment has no effect on Purchase Intention.